Holding on or letting go? Patient experiences of control, context, and care in oral esketamine treatment for treatment-resistant depression: A qualitative study - Breeksema, Joost J.; Niemeijer, Alistair; Kuin, Bouwe; Veraart, Jolien; Kamphuis, Jeanine; Schimmel, Nina; van den Brink, Wim; Vermetten, Eric; Schoevers, Robert (Frontiers in Psychiatry, 2022)
Background Ketamine and its enantiomer esketamine represent promising new treatments for treatment-resistant depression (TRD). Esketamine induces acute, transient psychoactive effects. How patients perceive esketamine treatment, and which conditions facilitate optimal outcomes, remains poorly understood. Understanding patient perspectives on these phenomena is important to identify unmet needs, which can be used to improve (es)ketamine treatments. Aims To explore the perspectives of TRD patients participating in ‘off label’ oral esketamine treatment. Methods In-depth interviews were conducted with 17 patients (11 women/6 men) after a six-week, twice-weekly esketamine treatment program or after six months of at-home use. Interviews explored participants’ perspectives, expectations, and experiences with esketamine treatment. Audio interviews were transcribed verbatim and analysed following an Interpretative Phenomenological Analysis (IPA) framework. Results Key themes included overwhelming experiences; inadequate preparation; letting go of control; mood states influencing session experiences; presence and emotional support, and supportive settings. Patients’ attempts to let go and give into vs. attempts to maintain control over occasionally overwhelming experiences was a central theme. Thorough preparation and education; consistent physical and emotional support; private, stimulus-free, comfortable surroundings, and music all influenced patients’ ability to give into the experience, impacting their mood and anxiety about future sessions. Conclusion Better preparation beforehand, an optimized treatment setting, and emotional and psychological support during (es)ketamine sessions can help patients to “let go” and may lead to better quality of care and outcomes. Recommendations to improve quality of patient care in (es)ketamine treatment are provided, including suggestions for the training of nurses and other support staff.